The effect of physiotherapy on anxiety, depression, and stress in chronic low back pain - F. Abbas, Mustafa; N. A. Al-Hussari, Zena; S. Mahmood, Abdullah (YCAB Publisher, 2024)
Background: Chronic low back pain has an impact on the patient’s life socially,financially, and psychologically, and little data is dealing with the effect of physiotherapy on improving this psychological burden. Objectives: to assess the effect of physiotherapy on depression, anxiety, and stress in those patients. Method: cross-sectional study was conducted at many of the neurology and physiotherapy clinics in Erbil (Iraq), with 40 patients who met the criteria of low back pain depending on the Back Pain Functional Scale, and for each patient, we determined the socio demographic characteristics and clinical ones. The anxiety, depression, andstress were assessed by the Depression, anxiety, and Stress Scale before and afterphysiotherapy. Results: of the 40 patients, there were 10 males (25 %), 19 were unemployed (47.5%), and 19 were uneducated (47.5%). There were 13 patients with another joint deformity (32.5%), and 34 patients were married. There was a significant improvement of depression (p=0.002) and improvement of anxiety (p=0.023), and the most significant was with improvement of stress (p=0.0001). Conclusion:physiotherapy can lead to the improvement of depression,anxiety,and stress in low back pain patients. Keywords:physiotherapy; anxiety; depression; stress; low back pain